Peran Orang Tua dalam Peningkatan Kualitas Pembelajaran di TK Pgri Merpati Pangandaran - Dea Anggriani; Ila Mustakimah; Mia Rahmawati; Shabilia Aulia Kurnia; Sesi Bandawati; Yayu Nuraidah Solihat (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2023)
The parents play a crucial role in early childhood education, particularly in optimizing children's learning experiences at the kindergarten level. This study involves parental participation in various activities and interactions with the school to enhance the quality of learning in kindergarten. The aim of this research is to understand the role of parents in improving the learning quality of children. The research employs a qualitative-descriptive model approach, which aims to describe a phenomenon or event that occurs. The methods used include observation and interviews. The findings of this study reveal that parents have an essential role in enhancing the learning quality at TK PGRI Merpati Pangandaran. Key aspects of parental involvement in improving learning quality lie in their ability to build attachment with their children and foster good communication between parents, children, and teachers. Moreover, parents who take the initiative to be involved in their child's education and create a conducive learning environment at home can motivate the child in the learning process. Contributing to the decision-making process at school and cooperating with the community are also crucial points to consider, as the quality of learning is the responsibility of all parties, especially parents. Therefore, parents are encouraged to continuously improve their skills, knowledge, and creativity to realize the importance of their role in achieving improved learning quality. By implementing all efforts optimally, the process of enhancing the quality of learning can be achieved promptly.